Transcriptomic Analysis of Staphylococcus aureus Under the Stress Condition Caused by Litsea cubeba L. Essential Oil via RNA Sequencing - Yang, Yunqiao; Chen, Yunru; Zhang, Geyin; Sun, Junying; Guo, Lei; Jiang, Mingsheng; Ou, Bingming; Zhang, Weiyu; Si, Hongbin (Frontiers in Microbiology, 2020)
Litsea cubeba L. essential oil (LCEO) is a natural essential oil with considerable antimicrobial activity, and it can gradually replace some chemical additives in food industry. However, the genetic evidences of stress response of bacteria under sub-lethal treatment with LCEO is limited. To this end, transcriptomic analysis of Staphylococcus aureus 29213 under low concentration of LCEO was performed. Bacterial RNA samples were extracted from 1/4 MIC (0.07 μL/mL) of LCEO-treated and non-treated S. aureus 29213. The transcriptional results were obtained by RNA sequencing (RNA-Seq). After treated with LCEO of S. aureus 29213, 300 and 242 genes were significantly up and down-regulated. Up-regulated genes were mainly related to cell membrane (wall) stress stimulon including genes related to two-component regulatory system (VraS), histidine metabolism (hisABCD etc.) and L-lysine biosynthesis (thrA, lysC, asd etc.). Significant difference were also founded between LCEO-treated and non-treated groups in peptidoglycan biosynthesis related pathways. Down-regulated genes were related to nitrogen metabolism (NarGHIJ etc.), carotenoid biosynthesis (all) and pyruvate metabolism (phdA, pflB, pdhC etc.) of S. aureus 29213 in an LCEO-existing environment compared to the control. At the same time, we confirmed that LCEO can significantly affect the staphyloxanthin level of S. aureus 29213 for the first time, which is closely related to the redox state of S. aureus 29213. These evidences expanded the knowledge of stress response of S. aureus 29213 strain under sub-lethal concentration of LCEO.